A dog bite study in a dog rabies-affected area in South Africa - Jacqueline Weyer; Chantel A. le Roux; Charles Kajese; Lucy Fernandes (Southern African Journal of Infectious Diseases, 2020)
Background: Rabies is an untreatable and highly fatal viral zoonosis. Despite the ability to control and prevent the disease, it is estimated that one person dies of rabies every 10 minutes in developing countries. However, the true burden of the disease remains undefined in most developing countries because of a lack of systematic surveillance. Dog bite data obtained from healthcare facilities where dog bite victims seek medical care may provide an additional source of information that can be used to inform the burden of disease and identify points for interventions for improved delivery of post-exposure prophylaxis (PEP) to prevent the disease.